Literature Study: Educational Management Strategies In Rural Schools: Studi Literatur: Strategi Manajemen Pendidikan Di Sekolah Pedesaan - Li Jin; Dian Hidayati (Journal of Multidisciplinary Science, 2023)
Educational resources are relatively scarce in rural areas, and many abandoned children are in rural areas. Therefore, it needs to be clarified in education and teaching. This study uses a qualitative method with a literature study approach. Data is taken in the form of books and journals taken from Google Scholar with specific keywords according to the needs of the article. From this study, it was found that improving the level of education and management of primary and secondary schools in rural areas is a problem that educators must consider and focus on. Primary and secondary schools should improve relations and update strategies based on different national policies to meet the needs of teaching reform. Improve implementation methods and education management strategies, and provide appropriate strategic support for managing primary and secondary schools in rural areas of different perspectives so that students can improve their cognition and enable them to receive a good education. Based on this, the effective strategy for managing rural primary and secondary education is mainly analyzed further.